Detection of some CC Chemokine Ligands in Patients with Cutaneous Leishmaniasis - Bayram, Duha Muhanad; Hassan, Ghuffran Muhammed; Ali, Hayder Zuhair (Iraqi Journal of Science, 2022)
Cutaneous leishmaniasis (CL) is an endemic parasitic disease found in many provinces of Iraq. The immune system plays a crucial role in the development or healing of lesions through chemotactic cytokine activity. This study was aimed to detect the levels of two chemokine ligands (CCL2 and CCL5) in Iraqi patients suffering from dermal ulcers, caused by cutaneous leishmaniasis. It was measured in pre and post-treatment state of Pentostam (Pentavalent Antimony 100 mg). Blood serum concentrations of CCL2, CCL5 were measured by enzyme-linked immunosorbent assay among newly infected patients, two-trial treatment patients and three-trial treatment patients, in comparison with the control group. The result indicated a significant difference in CCL5 level for the three groups of CL patients. Whereas the control (p˂0.5), CCL2 level counterparts showed a significant difference only in newly infected and the thee-trial treatment groups. Moreover, there was a significant difference between all CCL5 patient groups, while no observed difference was detected within patient groups of CCL2.Thus altering the chemokine levels before and after treatment gives insights for parasite role in chemokine expression which may help in new therapeutic approaches for dry or wet CL.